SPE water electrolysis anode catalyst layer with uniform network structure, preparation method and membrane electrode

By using alcohol -alcohol and deodorizing water hybrid solvents in the SPE electrolytic water anode catalytic layer, it is evenly mixed with the catalyst to solve the problem of uneven network structure of the catalytic layer and improves the performance and efficiency of electrolyte water.

CN117026288BActive Publication Date: 2025-01-28WUHAN UNIV OF TECH

Patent Information

Application Number
CN202310886395.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-28
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The network structure of the existing SPE electrolytic water anode catalytic layer is uneven, which leads to a decrease in the electron conductivity and proton conductivity of the catalytic layer, which in turn affects the performance and efficiency of the electrolytic water.

Method used

By mixing alcohol -ion water to mix the solvents, the whole fluorosamine resin ultrasonic is dispersed in a mixed solvent, the resin decentralization is prepared, and then the catalyst is added for ultrasound and ball milling to form a uniform catalyst slurry. Finally The heat treatment in the oven is used to remove the cleaning solvent and prepare anode catalytic layer with a uniform network structure.

Benefits of technology

The network structure distribution of the catalytic layer is realized, the performance and efficiency of electrolyte water are improved, and the process is simple and easy to apply for large -scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117026288B_ABST
    Figure CN117026288B_ABST
Patent Text Reader

Abstract

The present invention discloses a SPE water electrolysis anode catalyst layer with a uniform network structure, a preparation method and a membrane electrode, comprising: step 1: mixing alcohol and deionized water into a mixed solvent according to a designed ratio; step 2: ultrasonically dispersing a perfluorosulfonic acid resin in the mixed solvent configured above according to a designed ratio to obtain a resin dispersion; step 3: adding a catalyst to the prepared resin dispersion according to the designed ratio, ultrasonicating in a cell crusher under an ice bath state, and then ball milling in a ball mill to obtain a catalyst slurry with uniform resin mixing; step 4: coating or spraying the prepared catalyst slurry on a proton exchange membrane or a transfer substrate, placing the prepared CL in an oven for heat treatment, so as to remove the composite solvent in the CL, and obtaining a SPE water electrolysis anode catalyst layer with a uniform network structure. The present invention can effectively improve the uniformity of the network structure distribution of the catalyst layer, thereby improving the performance and efficiency of water electrolysis, and the method is simple and feasible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen energy and fuel cells, and specifically relates to a SPE water electrolysis anode catalyst layer with a uniform network structure, a preparation method and a membrane electrode. Background Art

[0002] Solid polymer electrolyte (SPE) water electrolysis is an efficient and clean hydrogen production technology with high product purity. It is the most promising large-scale hydrogen production technology and can be combined with intermittent energy sources (such as wind and solar energy) to achieve long-term large-scale energy storage. SPE water electrolysis has a large theoretical current density and high energy efficiency, and can directly store hydrogen through high-pressure operation without subsequent mechanical compression. It is a reliable, efficient and economical method for preparing green hydrogen, and an important method to accelerate my country's energy transformation and ensure my country's energy security.

[0003] Membrane electrode (MEA) is the core component of the SPE water electrolysis tank. Electrochemical hydrogen evolution (HER) and oxygen evolution reaction (OER) are two very important reactions occurring on the cathode and anode catalyst layers of the SPE water electrolysis hydrogen production membrane electrode, respectively. The HER reaction is simple and fast, while the OER reaction mechanism is more complex and dynamically slow, and is the controlling step of the electrolysis reaction. Therefore, the structure and performance of the anode catalyst layer have an important influence on the performance of the electrolyzer, especially the thin catalyst layer with low precious metal loading. The proton and electron conductivity of the anode catalyst layer is an important characteristic, but it is also a characteristic that is not considered in the current development of the catalyst layer. Currently, commercial anode catalyst layers are usually made by mechanically mixing and coating solvents, resins and catalysts. The resin plays the role of providing a proton transfer channel and fixing the catalyst in the catalytic layer, but the resin is easy to agglomerate during the catalyst slurry preparation process, which increases the particle size of the catalyst agglomerates. In addition, the resin has no electronic conductivity. The agglomerated resin causes the catalyst to form larger agglomerates, which not only reduces the electronic conductivity of the catalytic layer, but also fails to form an evenly distributed resin network structure to provide a fast proton conduction channel for the catalytic layer. In addition, after the catalyst slurry agglomerates, it cannot form uniform pores to provide channels for oxygen desorption, thereby reducing the activity and efficiency of the catalytic layer.

[0004] At present, the commercial SPE water electrolysis anode catalyst layer preparation method adopts the method of spraying or coating after mechanically mixing the solvent, resin and catalyst. The resin is not pre-dispersed, and the combination state of the resin and the catalyst cannot be controlled, so the network structure of the catalyst layer cannot be controlled, and it is difficult to further improve the efficiency and performance of the catalyst layer. In order to improve the performance of the catalyst layer, many researchers also load the catalyst on a conductive carrier or add conductive additives to the catalyst layer to achieve the purpose of improving the reaction activity. However, these methods are complicated and new problems arise after adding a new phase in the catalyst layer. At the same time, the problem of pore distribution of the catalyst layer is not solved. None of them achieves good performance and effect, and it is impossible to achieve large-scale application. Therefore, a method for preparing an anode catalyst layer without adding a new phase and with a simple process is needed to improve the uniformity of the distribution of the catalyst layer network structure, so as to achieve the high performance and efficiency of SPE water electrolysis. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, one of the objects of the present invention is to provide a method for preparing an SPE water electrolysis anode catalyst layer with a uniform network structure, which can effectively improve the uniformity of the network structure distribution of the catalyst layer, thereby improving the performance and efficiency of water electrolysis, and the method is simple and feasible.

[0006] Another object of the present invention is to provide a SPE water electrolysis anode catalyst layer having a uniform network structure.

[0007] Another object of the present invention is to provide a membrane electrode.

[0008] To achieve the above object, the present invention is implemented by the following technical solutions:

[0009] On the one hand, the present invention provides a method for preparing a SPE water electrolysis anode catalyst layer having a uniform network structure, comprising the following steps:

[0010] Step 1: Mix alcohol and deionized water according to the designed ratio to prepare a mixed solvent, so that the solubility parameter of the mixed solvent is close to the solubility parameter of the perfluorosulfonic acid resin;

[0011] Step 2: ultrasonically dispersing the perfluorosulfonic acid resin in the above-prepared mixed solvent according to the designed ratio to obtain a resin dispersion;

[0012] Step 3: Add the catalyst to the prepared resin dispersion according to the designed ratio, perform ultrasonic treatment in a cell crusher in an ice bath, and then perform ball milling in a ball mill to obtain a catalyst slurry uniformly mixed with the resin;

[0013] Step 4: Coat or spray the prepared catalyst slurry on the proton exchange membrane or the transfer substrate, and place the prepared catalyst layer (CL) in an oven for heat treatment to remove the solvent in the CL and obtain a SPE water electrolysis anode catalyst layer with a uniform network structure.

[0014] Preferably, in step 1, the mass ratio of the alcohol to the deionized water is (1:4) to (4:1).

[0015] Preferably, in step 1, the alcohol is selected from isopropanol, n-propanol, ethanol and methanol.

[0016] Preferably, in step 1, the solubility parameter calculation method of the mixed solvent is:

[0017] δ m =[(∑X i E coh,i ) / ∑X i V i ] 1 / 2

[0018] Among them, X i represents the molar ratio of solvent i, E coh,i represents the cohesive energy of solvent i, V i represents the molar volume of solvent i. The solubility parameters of the main chain and side chain of perfluorosulfonic acid resin are 9.7 and 16.45, respectively.

[0019] Preferably, in step 2, the mass ratio of the perfluorosulfonic acid resin to the mixed solvent is (1:2) to (2:1).

[0020] Preferably, in step 3, the mass ratio of the perfluorosulfonic acid resin to the catalyst is (1:30) to (3:7).

[0021] Preferably, in step 3, the solid content of the catalyst slurry is 2-40%.

[0022] Preferably, in step 3, the catalyst is selected from IrO2, RuO2, IrO2 / M, wherein M is other metals (such as Pt, Ir, etc.) or metal oxides or carriers (antimony-doped tin oxide, TiO2, etc.).

[0023] On the other hand, the present invention provides a SPE water electrolysis anode catalyst layer having a uniform network structure, wherein the SPE water electrolysis anode catalyst layer is prepared by the preparation method as described above.

[0024] In yet another aspect, the present invention provides a membrane electrode, comprising the SPE water electrolysis anode catalyst layer as described above.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The method currently used is to prepare the catalyst layer by directly mixing the resin, mixed solvent and catalyst into a slurry. The present invention pre-disperses the proton conductive resin and disperses the perfluorosulfonic acid resin in the mixed solvent by preparing a water-alcohol mixed solvent, thereby having the best catalyst layer network structure. The size of the ion clusters and the morphology of the proton transmission channel in the perfluorosulfonic acid resin are closely related to the mixed solvent used. The alcohol in the mixed solvent disperses the main chain of the resin, and the deionized water disperses the side chain of the resin, thereby affecting the binding state of the resin and the catalyst. The water-alcohol ratio of the mixed solvent is regulated by an alcohol solvent so that the resin and the catalyst are evenly mixed, thereby regulating the network structure of the catalyst layer so that the catalyst layer has a network structure with the best performance and efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a performance test result diagram of the anode catalyst layer prepared in Examples 1-4 of the present invention applied in the SPE water electrolysis fixture.

[0028] Figure 2 This is a diagram of the particle size of the resin and slurry after dispersion in Examples 1-4 of the present invention.

[0029] Figure 3 This is a scanning electron microscope image of the anode catalyst layer prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.

[0031] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0032] Embodiment 1:

[0033] Isopropyl alcohol and deionized water are mixed in a ratio of 2:1 to prepare a mixed solvent, and the perfluorosulfonic acid resin solution is dispersed in the mixed solvent prepared above, and the ratio of the resin to the mixed solvent is controlled to be 3:4. The resin dispersion is prepared by ultrasonic dispersion.

[0034] A certain mass of IrO2 catalyst was added to the prepared resin dispersion, the mass ratio of resin to catalyst was 1:9, the solid content of the catalyst slurry was 18%, and the catalyst slurry was prepared by ultrasonication in a cell crusher under ice bath condition and then ball milling in a ball mill. The prepared catalyst slurry was coated on a polytetrafluoroethylene (PTFE) sheet, and the coated CL was placed in an oven for heat treatment to remove the mixed solvent in the CL.

[0035] Embodiment 2:

[0036] The mixed solvent was prepared by mixing n-propanol and deionized water in a ratio of 2:1, and the perfluorosulfonic acid resin solution was dispersed in the mixed solvent prepared above, and the ratio of the resin to the mixed solvent was controlled to be 3:4. The resin dispersion was prepared by ultrasonic dispersion.

[0037] A certain mass of IrO2 catalyst was added to the prepared resin dispersion, the mass ratio of resin to catalyst was 1:9, the solid content of the catalyst slurry was 18%, and the catalyst slurry was prepared by ultrasonication in a cell crusher under ice bath condition and then ball milling in a ball mill. The prepared catalyst slurry was coated on the PTFE sheet, and the coated CL was placed in an oven for heat treatment to remove the mixed solvent in the CL.

[0038] Embodiment 3:

[0039] Ethanol and deionized water were mixed in a ratio of 2:1 to prepare a mixed solvent, and the perfluorosulfonic acid resin solution was dispersed in the mixed solvent prepared above, and the ratio of the resin to the mixed solvent was controlled to be 3:4. The resin dispersion was prepared by ultrasonic dispersion.

[0040] A certain mass of IrO2 catalyst was added to the prepared resin dispersion, the mass ratio of resin to catalyst was 1:9, the solid content of the catalyst slurry was 18%, and the catalyst slurry was prepared by ultrasonication in a cell crusher under ice bath condition and then ball milling in a ball mill. The prepared catalyst slurry was coated on the PTFE sheet, and the coated CL was placed in an oven for heat treatment to remove the compound solvent in the CL.

[0041] Embodiment 4:

[0042] Methanol and deionized water were mixed in a ratio of 2:1 to prepare a mixed solvent, and the perfluorosulfonic acid resin solution was dispersed in the mixed solvent prepared above, and the ratio of the resin to the mixed solvent was controlled to be 3:4. The resin dispersion was prepared by ultrasonic dispersion.

[0043] A certain mass of IrO2 catalyst was added to the prepared resin dispersion, the mass ratio of resin to catalyst was 1:9, the solid content of the catalyst slurry was 18%, and the catalyst slurry was prepared by ultrasonication in a cell crusher under ice bath condition and then ball milling in a ball mill. The prepared catalyst slurry was coated on the PTFE sheet, and the coated CL was placed in an oven for heat treatment to remove the compound solvent in the CL.

[0044] Embodiment 5:

[0045] Isopropyl alcohol and deionized water are mixed in a ratio of 1:4 to prepare a mixed solvent, and the perfluorosulfonic acid resin solution is dispersed in the mixed solvent prepared above, and the ratio of the resin to the mixed solvent is controlled to be 1:2. The resin dispersion is prepared by ultrasonic dispersion.

[0046] A certain mass of RuO2 catalyst was added to the prepared resin dispersion, the mass ratio of resin to catalyst was 3:7, the solid content of the catalyst slurry was 40%, and the catalyst slurry was prepared by ultrasonication in a cell crusher under ice bath condition and then ball milling in a ball mill. The prepared catalyst slurry was coated on the PTFE sheet, and the coated CL was placed in an oven for heat treatment to remove the compound solvent in the CL.

[0047] Embodiment 6:

[0048] Ethanol and deionized water were mixed in a ratio of 4:1 to prepare a mixed solvent, and the perfluorosulfonic acid resin solution was dispersed in the mixed solvent prepared above, and the ratio of the resin to the mixed solvent was controlled to be 2:1. The resin dispersion was prepared by ultrasonic dispersion.

[0049] A certain mass of IrO2 / TiO2 catalyst is added to the prepared resin dispersion, the mass ratio of resin to catalyst is 1:30, the solid content of the catalyst slurry is 5%, and the catalyst slurry is prepared by ultrasonication in a cell crusher in an ice bath, and then ball milling in a ball mill. The prepared catalyst slurry is sprayed on the PTFE sheet, and the sprayed CL is placed in an oven for heat treatment to remove the compound solvent in the CL.

[0050] Embodiment 7:

[0051] Ethanol and deionized water were mixed in a ratio of 4:1 to prepare a mixed solvent, and the perfluorosulfonic acid resin solution was dispersed in the mixed solvent prepared above, and the ratio of the resin to the mixed solvent was controlled to be 2:1. The resin dispersion was prepared by ultrasonic dispersion.

[0052] A certain mass of IrO2 / TiO2 catalyst is added to the prepared resin dispersion, the mass ratio of resin to catalyst is 3:7, the solid content of the catalyst slurry is 2%, and the catalyst slurry is prepared by ultrasonication in a cell crusher under ice bath condition and then ball milling in a ball mill. The prepared catalyst slurry is sprayed on the proton exchange membrane, and the sprayed CL is placed in an oven for heat treatment to remove the compound solvent in the CL.

[0053] Embodiment 8:

[0054] Take four cut Nafion212 membranes and transfer the cathode catalyst slurry onto each membrane. The cathode Pt loading is 0.4 mg Pt cm -2The catalyst layers in Examples 1, 2, 3, and 4 were transferred to the other side, and the IrO2 loading on the anode was 1.8 mg cm -2 The electrodes are numbered 1#, 2#, 3#, and 4# respectively.

[0055] Place electrodes 1#, 2#, 3#, and 4# into the SPE water electrolysis fixture for testing. The test conditions are as follows: battery temperature 80°C, water flow rate 40ml min -1 , performance test results are attached Figure 1 The particle size diagram of the dispersed resin and slurry in Examples 1, 2, 3, and 4 is shown in the attached Figure 2 The prepared catalytic layer scanning electron micrograph is shown in the attached Figure 3 shown.

[0056] from Figure 1 It can be seen that the catalyst layer prepared by dispersing the resin with the mixed solvent prepared by isopropanol in Example 1 has the best performance at 2A / cm 2 Under the electric density, the electrolysis voltage is 1.76V, followed by the catalyst layer prepared by dispersing the resin with the mixed solvent prepared by n-propanol, ethanol, and methanol. The solubility parameters of the mixed solvents in Examples 1, 2, 3, and 4 are 16.9, 17.0, 17.5, and 18.5, respectively. The solubility parameter of isopropanol is closest to the main chain and side chain of the perfluorosulfonic acid resin, and the main chain and side chain of the resin can be well dispersed. The prepared resin and catalyst slurry have a smaller particle size ( Figure 2 ), because the prepared catalyst layer network structure is relatively uniform ( Figure 3 ), and at the same time, it has more mesopores and macropores to provide channels for the transmission of water and oxygen, so the electrode has the best performance in water electrolysis.

[0057] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a SPE water electrolysis anode catalyst layer having a uniform network structure, characterized in that: The steps include: Step 1: Mix alcohol and deionized water according to the designed ratio to prepare a mixed solvent, so that the solubility parameter of the mixed solvent is close to the solubility parameter of the perfluorosulfonic acid resin; the alcohol is selected from isopropanol, n-propanol, ethanol, and methanol; The solubility parameters of mixed solvents are calculated as follows: d m =[(ΣX i E coh,i ) / ΣX i V i ] 1 / 2 Among them, X i represents the molar ratio of solvent i, E coh,i represents the cohesive energy of solvent i, V i represents the molar volume of solvent i; Step 2: ultrasonically dispersing the perfluorosulfonic acid resin in the above-prepared mixed solvent according to the designed ratio to obtain a resin dispersion; Step 3: Add the catalyst to the prepared resin dispersion according to the designed ratio, perform ultrasonic treatment in a cell crusher in an ice bath, and then perform ball milling in a ball mill to obtain a catalyst slurry uniformly mixed with the resin; Step 4: Coat or spray the prepared catalyst slurry on the proton exchange membrane or the transfer substrate, place the prepared catalyst layer in an oven for heat treatment, remove the solvent in the catalyst layer, and obtain an SPE water electrolysis anode catalyst layer with a uniform network structure.

2. The method for preparing the SPE water electrolysis anode catalyst layer with a uniform network structure according to claim 1, characterized in that: In step 1, the mass ratio of the alcohol to the deionized water is (1:4) to (4:1).

3. The method for preparing the SPE water electrolysis anode catalyst layer with a uniform network structure according to claim 1, characterized in that: In step 2, the mass ratio of the perfluorosulfonic acid resin to the mixed solvent is (1:2) to (2:1).

4. The method for preparing the SPE water electrolysis anode catalyst layer with a uniform network structure according to claim 1, characterized in that: In step 3, the mass ratio of the perfluorosulfonic acid resin to the catalyst is (1:30) to (3:7).

5. The method for preparing the SPE water electrolysis anode catalyst layer with a uniform network structure according to claim 1, characterized in that: In step 3, the solid content of the catalyst slurry is 2-40%.

6. The method for preparing the SPE water electrolysis anode catalyst layer with a uniform network structure according to claim 1, characterized in that: In step 3, the catalyst is selected from IrO2, RuO2, IrO2 / M, wherein M is other metals or metal oxides or carriers.

7. A SPE water electrolysis anode catalyst layer having a uniform network structure, characterized in that: The SPE water electrolysis anode catalyst layer is prepared by the preparation method described in any one of claims 1-6.

8. A membrane electrode, characterized in that: It comprises the SPE water electrolysis anode catalyst layer as described in claim 7.

Citation Information

Patent Citations

  • Preparation method for catalyst slurry for solid polymer electrolyte water electrolysis membrane electrode

    CN108579818A

  • Catalyst slurry preparation method, catalyst slurry, catalyst coating membrane and membrane electrode

    CN114188548A

Cited By

  • Uniform coating slurry and method suitable for different space preparation

    CN121321022A